Minimum and Stable Coefficient of Thermal Expansion by Three-Step Heat Treatment of Invar 36 - Mehmet Kul; Bekir Akgül; Yusuf Ziya Karabay; Leonhard Hitzler; Enes Sert; Markus Merkel (Crystals)
The low coefficient of thermal expansion of Invar 36 represents a significant consideration in light of its potential effects, particularly in industrial applications where thermal stability is of paramount importance. In light of this, a three-step heat treatment was employed, to reduce the thermal expansion coefficient, and enhance the thermal dimensional stability. The ingots produced by vacuum induction melting were subjected to a warm-rolling process at 900 °C, followed by a three-step heat treatment consisting of water quenching at 850 °C, tempering at 350 °C with a holding time of 1 h, and aging at 100 °C for 24 h. This process enabled the coefficient of thermal expansion to remain almost unchanged, exhibiting values between 0.5 and 0.6 × 10−6/°C up to 150 °C. Following the heat treatment, the total elongation increased up to 40% as a natural consequence of the reduction of residual stresses, while a slight decrease in tensile strength was observed. The implementation of a three-step heat treatment process has facilitated an enhancement of the soft magnetic property, which has exhibited a decline in coercivity and an increase in saturation magnetization. As a consequence, three-step heat-treated Invar 36 alloys are emerging as a potential candidate for utilization in the aerospace and precision electronics industries, given their satisfactory physical and mechanical characteristics.